Child and adolescent mental health services in the Western Cape of South Africa: policy evaluation, situational analysis, stakeholder perspectives, and implications for health policy implementation - Mokitimi, Stella (Department of Psychiatry and Mental Health, 2021)
In spite of the need for child and adolescent mental health (CAMH) services across the globe, very little has been done to develop and strengthen CAMH in low- and middle-income countries (LMIC). South Africa is an example of an LMIC where CAMH services have been very limited as a result of various potential factors, including the legacy of apartheid, stigma associated with mental health, and lack of priority of CAMH. In this thesis, we set out to generate an evidence-base about CAMH services in one South African province to inform service strengthening across the full healthcare system through policy development and implementation. We proposed that a comprehensive understanding of specific services requires a multilevel exploration of ‘hardware' (structural) and ‘software' (social) elements in the health systems that support these services. We started by reviewing the CAMH policy landscape with an analysis of the current state of policy development and implementation at national and provincial levels in all nine provinces of South Africa. Using the Walt and Gilson policy analysis triangle (1994), we examined the content, context, processes and actors involved in mental health or CAMH-specific policies. We then evaluated the hardware and software elements of CAMHS in the Western Cape Province by performing a situational analysis using the WHO-AIMS version 2.2 of 2005 (Brief version) adapted for the South African context and to CAMHS. We proceeded to seek the perspectives of stakeholders within the province – firstly a SWOT analysis with senior stakeholders, and secondly, qualitative analysis of the perspectives of grassroots service providers, and of parents/caregivers and adolescent service users. We collected information from these stakeholder groups through a stakeholder engagement workshop, focus group discussions and semi-structured individual interviews. Using the World Health Organization (WHO) (2007) and Gilson (2012) health systems frameworks, we reviewed both the hardware and the software elements of CAMH services and concluded with a synthesis of findings to provide a set of recommendations for policy development and service strengthening based on the evidence generated. In terms of service delivery, findings showed that child and adolescent mental health services (CAMHS) in the Western Cape were provided at all levels of care (primary, secondary and tertiary) and, at least at inpatient and outpatient level, based on catchment/geographical service areas. However, CAMHS were still limited and were provided under very resource-constrained conditions by inadequately trained service providers. In terms of the health workforce, CAMHS were provided by a range of professionals including child & adolescent psychiatrists, general psychiatrists, medical officers, clinical psychologists, social workers, mental health nurses, occupational therapists, and speech and language therapists. However, multidisciplinary expertise and psychosocial interventions were only available in specialist CAMHS at tertiary level of care. In addition, the specialist services were all based in the City of Cape Town, with no direct access to specialist CAMHS at secondary levels of care or in any of the rural districts of the province. Health information systems were not fit-for-purposes to generate disaggregated data on under-18-yearolds, thus made it extremely difficult to provide a comprehensive view of CAMHS in the province. In terms of access to essential medicines, basic classes of psychiatric medications were available at all levels of care, but not consistently so. An exploration of financing showed that no ring-fenced or disaggregated budgets were available for CAMHS, thus making it impossible to comment on the appropriateness of funding for the mental health needs of children and adolescents. In terms of leadership and governance, a national CAMH policy existed, but no implementation plans had been developed since the publication of the CAMH policy in 2003. Our findings highlighted a lack of dedicated CAMH leadership and governance in the province. We argued that the absence of a clear CAMH leadership structure also explained why provincial plans and strategies had not been developed and implemented over the last two decades. A very consistent finding from our data was a need for a dedicated provincial lead for CAMH. We concluded the thesis with hardware and software recommendations for policy implementation, service development, training and research.